Environmental Performance of a 7.5 KW Air/Water Heat Pump - Abeliotis, Konstadinos; Founta, Konstantia (Journal of Environmental Accounting and Management, 2026)
Heat pumps are mechanical devices that can be used for the sustainable generation of heating and cooling energy. However their construction generates also environmental burdens. The aim of this manuscript is the identification of the environmental hot spots of a air/water heat pump via means of life cycle assessment. Inventory data were collected by primary sources. The results indicate that the case of the heat pump, made of stainless steel, is the dominant contributor to the environmental impacts generated by the construction of the heat pump. Moreover, the main impact category affected by the heat pump components is that of human toxicity.